Leveling Up Language Skills: Higher Students’ Perspective on Google Docs as a Tool for English learning - Rani Maharani; Serlin Sepriyanti Dohare; Tharysa Rizqika Putri; Kusumawardhani, Ayuning Dyah (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
The research discusses the perceptions of students using Google Docs as a collaborative tool to enhance their writing skills in English. The study employed an online survey using Google Forms, conducted on 50 students from the English education program at Indraprasta University PGRI in the 2021 academic year. The survey results indicated that most respondents found Google Docs to be very useful in collaborative writing practice. They also highlighted the importance of features such as spell checking and real-time revision in supporting the writing process. The study concludes that there is a need for more comprehensive usage guides and training to overcome technical barriers and maximize the potential of Google Docs in improving writing and collaboration skills among college students